The Outside In: Art and the “Non-Aesthetic” - Hartnoll, Louis (The Nordic Journal of Aesthetics, 2025)
This essay proposes a case for grasping “Marxist aesthetics” as a generalised philosophical approach to the study of art and experience that underscores the pertinence of the “external” logic of capital. Such a logic, as this essay will develop through an account of arguments developed by Theodor W. Adorno and Peter Gorsen, must be seen to apply to both the history of aesthetics as a subdiscipline and the objects that aesthetics purports to study. The first part of the essay reconstructs the double crisis of aesthetics and art as figured in Adorno’s Aesthetic Theory, focusing on how this was heightened in the post-war period through the increasing incursion of “non-art” and the “non-aesthetic” into the artwork. As Adorno therein argues, a dialectical philosophical aesthetics should negotiate this double crisis through the assessment of aesthetic categories in their decline. After demonstrating how this plays out in his theory of the double character of art, the essay then outlines Gorsen’s notion of the de-aestheticisation of art, by which he seeks to analyse mid-century artistic practice as post-avant-garde. For Gorsen, de-aestheticised art rehearses the attempt by the historic avant-garde to abolish the distinction between art and life in the absence of widespread and organised revolutionary political movements. Tracing these arguments, the essay concludes with a brief case for fostering a “Marxist non-aesthetics,” understood as the inscription of historical and social contradictions into aesthetics in order to remain with, rather than abandon, such contradictions.